Molecular Screening of Rice Cultivated in Benin for the Identification of Xanthomonas oryzae Pv. oryzae and Bacterial Leaf Blight Resistance Genes. - MISSIHOUN, ANTOINE ABEL HOUMÈNOU (My University, 2023)
One of the most devastating diseases of rice worldwide is bacterial blight (BLB) caused by Xanthomonas oryzae pv. Oryzae (Xoo). In Benin, Xoo was first described in 2013 on wild rice Oryzae longistaminata. So far, no study has been done on Beninese Xoo strains. We do not know whether the pathogen has already passed into the rice varieties grown, or if they are exposed to How to cite this paper: Nanoukon, C.N.M., Hambada, K.D.M., Missihoun, A.A., Déguénon, K.L., Loumédjinon, B.M.P.F., Bio, B.W.D.F., Zinsou, E., Houngbélagnon, R.G.F., Havivi, A.S., Baba-Moussa, L. and Djédatin, L.G. (2023) Molecular Screening of Rice Cultivated in Benin for the Identification of Xanthomo- other bacteria. Whereas the use of resistant varieties, carrying resistance genes, is the only highly effective and environmentally friendly way to control this disease, no information is available on these Xoo resistance genes in rice varieties grown in Benin apart from the one we recently. This study aims to identify Beninese Xoo strains, causing BLB and screen rice varieties grown in Benin for the main resistance genes. Diseased rice leaves showing typical symptoms of fire blight collected from different rice fields in the three phytogeographic areas of Benin were analyzed by PCR for Xoo-specific sequence identification. Furthermore, seventy-five collected rice accessions were screened nas oryzae Pv. oryzae and Bacterial Leaf Blight Resistance Genes. Advances in Bioscience and Biotechnology, 14, 514-533. https://doi.org/10.4236/abb.2023.1412036 Received: October 15, 2023 Accepted: December 18, 2023 Published: December 21, 2023 to identify xa5, Xa7, xa13, and Xa21 resistance genes to Xoo. The results reveal that Xanthomonas oryzae was identified in two fields in Banikouara and one in Malanville. On the other hand, Sphingomonas sp. has been identified in several other rice fields in Benin. Forty-seven of seventy-five rice accessions examined (62.66%) carried Xoo resistance genes with 3 (4%) and 40 (53.33%) of xa5 and Xa21 respectively. None of the accessions had either Xa7 or xa13 resistance genes. Three accessions possess both xa5 and Xa21 genes. Isogenic lines IRBB60 and IRBB21, supposed to be a positive control, presented a Xoo sensitivity allele. These results indicate that Xoo has moved from the wild rice variety to the cultivated variety in northern Benin and varietal improvement programs must be implemented with varieties having several resistance genes for the efficient response against a possible BLB pandemic in Benin.
Keywords: Bacterial Blight; Xanthomonas oryzae Pv. oryzae; Molecular Characterization; Resistance Genes